2022
DOI: 10.1136/jnnp-2021-327462
|View full text |Cite
|
Sign up to set email alerts
|

CAIDE dementia risk score relates to severity and progression of cerebral small vessel disease in healthy midlife adults: the PREVENT-Dementia study

Abstract: BackgroundMarkers of cerebrovascular disease are common in dementia, and may be present before dementia onset. However, their clinical relevance in midlife adults at risk of future dementia remains unclear. We investigated whether the Cardiovascular Risk Factors, Ageing and Dementia (CAIDE) risk score was associated with markers of cerebral small vessel disease (SVD), and if it predicted future progression of SVD. We also determined its relationship to systemic inflammation, which has been additionally implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Inflammation has been linked to risk of ischemic strokes [41] and white matter disease on neuroimaging [ 42 , 43 ], which in turn has been linked to MCR [44] . The relationship of vascular risk factors and inflammation is bidirectional with higher vascular risk predicting progression of inflammation as well as white matter hyperintensities on neuroimaging [45] . However, Eastern and Western general populations have different anatomical distributions of small vessel disease [46] ; suggesting population specific factors that may determine pathogenesis of MCR regionally.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation has been linked to risk of ischemic strokes [41] and white matter disease on neuroimaging [ 42 , 43 ], which in turn has been linked to MCR [44] . The relationship of vascular risk factors and inflammation is bidirectional with higher vascular risk predicting progression of inflammation as well as white matter hyperintensities on neuroimaging [45] . However, Eastern and Western general populations have different anatomical distributions of small vessel disease [46] ; suggesting population specific factors that may determine pathogenesis of MCR regionally.…”
Section: Discussionmentioning
confidence: 99%
“…For the emotion of positive surprise, the recognition of which is also included in the Total Emotion Recognition score, it has also been found that regions involved in uncertain event recognition and processing, amygdala and insula as well as the parahippocampal, fusiform, and postcentral gyri [ 67 ], are directly affected in MCI pathology. Given that most people in the MCI group were aMCI, it must be noted that according to recent research aMCI subtypes with medial temporal lobe dysfunction perform worse in emotion recognition compared to other MCI subtypes; moreover, it has even been argued that emotion recognition is a sensitive and reliable indicator of their differential diagnosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond SVD, inflammation has recently been proposed as a possible pathogenic mechanism mediating the effect of vascular risk factors on the small cerebral arteries [ 79 ] implicated in neurodegeneration [ 80 ]. A recent study [ 42 ] has shown that lower education was the main predictor of increasing levels of systemic inflammation. Furthermore, an association between age, hypertension and inflammation has already been shown [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations